MODEL REFORMASI BIROKRASI PELAYANAN PUBLIK DENGAN PENDEKATAN ISO 9001-2008 TERHADAP KINERJA RUMAH SAKIT - Ni Nyoman Putri Sriadi (Jurnal Manajemen dan Bisnis, 2013)
Bureaucratic reform institution publication service that aims to improve the quality ofpublic services is principally the government's efforts to improve the quality of the threeaspects of the pattern of administration (management), human resources, and public serviceinstitutions. ISO 9001-2008 is a model of management system which has been proveneffective for improving the quality of an organization's performance. In this regard, ISO9001-2008 can be used as a model to facilitate the implementation of bureaucratic reform.This study aims to identify and analyze the implementation of the reform of the public servicebureaucracy of the application of ISO 9001-2008 for hospital performance improvement. Theresearch was conducted at public hospital of Wangaya, Denpasar, and the data analysistechniques uses the SEM results showed that the bureaucratic reform of public services has asignificant direct influence and positive impact on the hospital performance by 55.2%, whilethe remaining 44, 8% is influenced by variables other than the variable of bureaucraticreform of public services. ISO 9001-2008 has a positive impact of 53.9% while the remaining46.1%, is influenced by variables of other than the variable of ISO 9001-2008. ISO 9001-2008 has a positive influence on the reform of public service bureaucracy of 96.3% while theremaining 3.7% is influenced by variables of other than the variable of ISO 9001-2008.ISO 9001-2008 has a positive influence on the performance of the hospital throughbureaucratic reform of public service of 53.1%, while the remaining 46.95% is influenced byvariables of other than the variable of ISO 9001-2008. From the results of partial analysisthrough structural equation of SEM showed that after modification through models, it hasbeen obtained a better model than the results of the first model, because it has met six of theeight of the criteria of Goodness of Fit, namely the criteria of Chi-square (?2) of 1426, 610,RMSA of 0,078 Probability of 000, Relative Chi-square (?2/df) of 2.029, CFI of 0.953, andTLI of .961 in marginal conditions.Keywords: reform of public service bureaucracy, ISO 9001-2008, hospital performance